2015
DOI: 10.1002/ange.201505798
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arrestin on the Photodecay of Bovine Rhodopsin

Abstract: Continued activation of the photocycle of the dim-light receptor rhodopsin leads to accumulation of all-trans-retinal in rod outer segments (ROS). This accumulation can damage the photoreceptor cell. For retinal homeostasis, deactivation processes are initiated in which the release of retinal is delayed. One of the processes involves binding of arrestin to rhodopsin. Here, we investigate the interaction of pre-activated truncated bovine visual arrestin (Tr) with rhodopsin in 1,2diheptanoyl-sn-glycero-3-phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previous in vitro work has suggested that recombinant arrestin can stabilize Meta II, block the Meta III formation, or shift the Meta II/III equilibrium toward Meta II and inhibit the overall rate of all-trans retinal release (Sommer and Farrens, 2006). However, other findings instead suggest the stabilization of Meta III by either full-length arrestin (Burns et al, 2006) or its truncated form, Arr Tr , which is similar to physiologically relevant splice variant p44 (Chatterjee et al, 2015). A major caveat of these biochemical experiments is that they were performed with either detergent-solubilized rhodopsin or purified rod outer segment membranes, in which concentrations of added protein components (and the overall metabolic state of the system) are substantially different from those in intact cells.…”
Section: Arr1 and Grk1 Modulate The Decay Of Photoactivated Rhodopsinmentioning
confidence: 95%
“…Previous in vitro work has suggested that recombinant arrestin can stabilize Meta II, block the Meta III formation, or shift the Meta II/III equilibrium toward Meta II and inhibit the overall rate of all-trans retinal release (Sommer and Farrens, 2006). However, other findings instead suggest the stabilization of Meta III by either full-length arrestin (Burns et al, 2006) or its truncated form, Arr Tr , which is similar to physiologically relevant splice variant p44 (Chatterjee et al, 2015). A major caveat of these biochemical experiments is that they were performed with either detergent-solubilized rhodopsin or purified rod outer segment membranes, in which concentrations of added protein components (and the overall metabolic state of the system) are substantially different from those in intact cells.…”
Section: Arr1 and Grk1 Modulate The Decay Of Photoactivated Rhodopsinmentioning
confidence: 95%